Extraglomerular immune complex deposition in lupus nephritis. (January 2022) - Papa, Valentina; Brainer, James; Henriksen, Kammi J; Cenacchi, Giovanna; Chang, Anthony
Background: Lupus nephritis (LN) is a common manifestation and a major cause of morbidity and mortality in systemic lupus erythematosus (SLE) patients. It is characterized by glomerular and often extraglomerular immune complex deposition. Purpose: Given the emerging importance of the tubulointerstitial compartment, we conducted a retrospective study of 78 LN biopsies to enumerate the spectrum of extraglomerular immune complex deposition that can be observed in lupus nephritis by electron microscopy and to identify possible clinical or pathologic correlates. Results: The presence of tubulointerstitial immune complex deposition often accompanied interstitial inflammation, but some discrepancies were also seen. Conclusions: As target antigens are identified, correlation with glomerular, tubulointerstitial, and vascular immune complex deposition will be of increasing interest.